Quantification and the sources identification of total and insoluble hexavalent chromium in ambient PM: A case study of Aktobe, Kazakhstan. (November 2022) - Adotey, Enoch K.; Burkutova, Lyailya; Tastanova, Lyazzat; Bekeshev, Amirbek; Balanay, Mannix P.; Sabanov, Sergei; Rule, Anna M.; Hopke, Philip K.; Amouei Torkmahalleh, Mehdi
Abstract: Hexavalent chromium (Cr(VI)), a known carcinogen, emanates from both anthropogenic and natural sources. A pilot study of the ambient Cr(VI) concentrations was conducted at the center of Aktobe which is a few kilometers away from major industrial chromium plants. Total Cr(VI) concentrations were measured in the fall and winter seasons with mean values (S.D) of 5.30 (2.16) ng/m 3 and 2.26 (1.80) ng/m 3, respectively. Insoluble Cr(VI) levels were 4.80 (1.96) and 2.19 (1.75) ng/m 3 for the fall and winter, respectively. The total and insoluble Cr(VI) concentrations in the fall season were significantly higher than in winter, likely due to the higher rate of Cr(III) oxidation in the presence of ozone and ROS in fall compared to the rate of Cr(VI) reduction in the presence of VOCs at higher temperatures. On average, total Cr(VI) constituted 34.49% of the total Cr concentrations suggesting that the dominant valence state of Cr in the atmosphere is Cr(III). The previous reference values of exposure to Cr(VI) must be revisited by taking into account the insoluble Cr(VI) concentration since it is more prevalent in the atmosphere compared to soluble Cr(VI). The influence of the chromium plants as potential sources was not obvious in this study. Graphical abstract: Image 1 Highlights: Gas-solid reaction in ambient PM is essential to understand fully the Cr chemistry. Total Cr(VI) is dominated by insoluble Cr(VI). Toxicity of Cr(VI) should be based on insoluble Cr(VI) fraction. CBPF plots are essential tools to identify potential Cr(VI) sources. This study provides new data about ambient concentrations of insoluble Cr(VI).